Aphids‐induced plant volatiles affect diel foraging behavior of a ladybird beetle Coccinella septempunctata. (19th November 2019) - Norkute, Milda; Olsson, Ulf; Ninkovic, Velemir
Abstract: The ladybird beetle Coccinella septempunctata (L.) is an important biocontrol agent of pests such as various aphid species. Despite being one of the most studied coccinellid species, many aspects of its foraging behavior are still not completely understood. This study focuses on the diel foraging behavior of C. septempunctata, investigating their olfactory orientation toward aphid‐infested plants, walking activity on plants and on the soil, and feeding rates. In the scotophase the ladybird beetles were significantly more attracted to the odor of aphid‐infested plants, on which they also showed considerably higher walking activity then on uninfested controls. Females were more prone to utilize olfactory cues when searching for prey and fed at higher rates than males; this shows that they are better adapted to nocturnal activity, as they require higher food intake. Coccinella septempunctata have the same feeding rate during the scotophase as in the photophase. Our study shows that C. septempunctata has the potential to forage in the scotophase if prey is abundant. The results support the hypothesis that volatiles of aphid‐infested plants can attract or arrest foraging adult ladybird beetles, even in the darkness, which makes a considerable contribution to efficient prey search and enhances feeding capacity.